The Starunia collections in the Natural History Museum of the National Academy of Sciences of Ukraine in Lviv - Chornobay, Yuriy M.; Drygant, Daniel M. (Geotourism/Geoturystyka)
In the Natural History Museum of the National Academy of Sciences of Ukraine in Lviv there is a collection of a famous Pleistocene mammoth and a woolly rhinoceros, the so-called “first rhinoceros” from Starunia. The mammoth and the first rhinoceros were found 102 years ago, on 5th October and 6th November, 1907, respectively, in a shaft of an ozokerite (earth wax) mine near Starunia village (the Eastern Carpathians). The discovery of large Pleistocene mammals in Starunia was a spectacular, worldfamous scientific event. Beside the mammoth and the rhinoceros, many specimens of Pleistocene flora and fauna from Starunia and other places of the Fore-Carpathian region are exhibited in the Lviv Natural History Museum.